Behaviour of plain concrete beam under sinusoidal dynamic load / Roslan Mohammad (Faculty of Civil Engineering, 1997)
The study of the behaviour of plain concrete beam under sinusoidal dynamic load as well as static loading with respect to the serviceability and ultimate limits is undertaken. A total of four (4) beams with minimum strength of 60 N/mm² had been cast. One beam underwent static load test to failure. The purpose of this test is to determine the yield load of the beams, hence 50% of the yield load will be the mean load for dynamic test. Only two beams underwent sinusoidal repeated load with specified mean load. One specimen underwent one million cycles and another three million cycles.